(untitled) (Proceedings of International Educators Conference, 2024)
Cadets occupy mathematical objects, mathematical examples in the study of processes, and methods for solving problems. In this process, cadets are required to know, understand the corresponding mathematical concepts, apply them in the implementation of practical actions. This thesis examined the same process.